2019
DOI: 10.1103/physrevb.100.014401
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport as a probe of phase transformations in metallic antiferromagnets: The case of UIrSi3

Abstract: The electrical resistance, Hall resistance and thermoelectric power of the Ising-like antiferromagnet UIrSi3 were measured as functions of temperature and magnetic field. We have observed that the unequivocally different characters of first-order and second-order magnetic phase transitions lead to distinctly different magnetotransport properties in the neighborhood of corresponding critical temperatures and magnetic fields, respectively. The magnetic contributions to the electrical and Hall resistivity in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
5
12
0
Order By: Relevance
“…It was also found that magnon transport around the phase transition of antiferromagnetic NiO layer 35 facilitates magnon-mediated spin torque switching. Furthermore, antiferromagnet-based thermoelectrics [36][37][38][39] has seen a surge in interest lately. Here, we investigate the thermoelectric response of IrMn/CoFeB near the IrMn critical temperature.…”
mentioning
confidence: 99%
“…It was also found that magnon transport around the phase transition of antiferromagnetic NiO layer 35 facilitates magnon-mediated spin torque switching. Furthermore, antiferromagnet-based thermoelectrics [36][37][38][39] has seen a surge in interest lately. Here, we investigate the thermoelectric response of IrMn/CoFeB near the IrMn critical temperature.…”
mentioning
confidence: 99%
“…For the measurements, we used pieces of a single crystal grown by the floating zone melting method in a commercial four-mirror optical furnace with halogen lamps, each 1kW (model FZ-T-4000-VPM-PC, Crystal Systems Corp., Japan), being part of the previous studies [16,17]. A polycrystalline precursor was synthesized by arc-melting from stoichiometric amounts of the pure elements U (3N, further treated by Solid-State Electrotransport [19,20]), Ir (4N), and Si (6N) in Ar (6N) protective atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…A large single crystal of the cylindrical shape with length 50 mm and diameter of 4 mm was obtained. The details of the preparation are discussed in [17]. The high quality and orientation of the single crystal were verified by the Laue method (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously studied AFM materials [41][42][43], the disappearance of the hysteresis has been considered as one of the signatures of a tricritical point (TCP) in the phase diagram which separates first-and second-order AFM transitions and exhibiting Ising-type anisotropy [42,[44][45][46][47]. This supports the existence of TCP in U2Rh2Pb around Ttc = 13 K and µ0Htc = 4 T. It should be pointed out that TCP is an inherent feature of a broad class of antiferromagnets, in which the metamagnetic transition at low temperatures is of the first-order type and magnetic critical point in zero field is of the second-order type, and hence does now imply any temperature variations of magnetic interactions [48].…”
Section: Magnetic Phase Diagrammentioning
confidence: 99%